2007
DOI: 10.1177/0961203307083179
|View full text |Cite
|
Sign up to set email alerts
|

Association of the nitric oxide synthase (eNOS) gene polymorphism with increased risk for both lupus glomerulonephritis and rheumatoid arthritis in a single genetically homogeneous population

Abstract: Nitric oxide (NO), a short-lived gaseous free radical, synthesized from L-arginine by NO synthases (NOS), is a potent mediator of biologic responses involved in the pathogenesis of autoimmune rheumatic diseases, such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Most biological necessary NO is produced by the family of three NOS. To date, several functionally relevant genetic polymorphisms in the eNOS gene have been associated with various vascular, infectious and autoimmune diseases. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Most of these studies are small cohort studies and await confirmation by larger multi-ethnic cohort studies [58]. A recent study from Greece found an association between NOS3 polymorphisms and lupus nephritis [59]. These genetic studies further support the view that the effects of RNIs and ROIs on disease are significantly affected by the biological setting in which they are produced and the overall production of RNIs compared with ROIs.…”
Section: Polymorphisms In Nos In Human Slesupporting
confidence: 53%
“…Most of these studies are small cohort studies and await confirmation by larger multi-ethnic cohort studies [58]. A recent study from Greece found an association between NOS3 polymorphisms and lupus nephritis [59]. These genetic studies further support the view that the effects of RNIs and ROIs on disease are significantly affected by the biological setting in which they are produced and the overall production of RNIs compared with ROIs.…”
Section: Polymorphisms In Nos In Human Slesupporting
confidence: 53%
“…Conflicting results were reported for the Turkish population in which the 4a and 4aa alleles were shown to be associated with susceptibility to SLE [36]. A single study of the Greece population by Vazgiourakis et al 2007 showed a significant association of the 27 bp VNTR with RA [18]. Previously, a possible relationship between the synthesis of nitric oxide by the eNOS gene and immune dysregulation in the thyroid gland was reported by Varul et al [10].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of allelic frequency revealed a significant association of the 4b allele with susceptibility to SLE (p = 0.009) and the 4bb genotype to SLE (p = 0.008) and HT (p = 0.05). As shown in Table 4, this polymorphism (4b/4bb) has been associated with SLE in Colombian populations [28], while three other populations (USA, Korea and Greece) failed to show a significant association [18,29,35]. Conflicting results were reported for the Turkish population in which the 4a and 4aa alleles were shown to be associated with susceptibility to SLE [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations